TUGAS BAWASLU KOTA KUPANG DALAM PENGAWASAN PEMILU ANGGOTA DPRD KOTA KUPANG MASA JABATAN 2024-2029 - Frely Anugrah Day; Josef Mario Monteiro; Agnes Doortji Rema (Petitum Law Journal, 2026)
General elections are an important foundation of democracy to ensure people's representation in legislative institutions. Election supervision is a crucial element so that elections are honest, fair, and democratic. This study aims to analyze the implementation of the duties of the Kupang City Election Supervisory Agency in supervising the 2024–2029 Kupang City Member General Election and identify factors that inhibit the effectiveness of supervision. The study uses an empirical legal approach with socio-legal and conceptual methods. Data were collected through interviews with the Chairperson and members of General Election Supervisory Body, legislative candidates, literature studies, and field documentation in Kota Raja District. The results of the study show that Bawaslu has been active and collaborative in supervision, through the formation of working groups, cross-institutional cooperation, and direct and administrative supervision methods. However, there are obstacles such as limited personnel, low community participation, and weak coordination between organizing institutions. The study concludes that the effectiveness of supervision is influenced by the readiness of human resources, institutional support, and community participation. It is necessary to strengthen the role of General Election Supervisory Body through training, legal counseling, and synergy with the General Election Commissions and law enforcement officers in order to create elections with integrity.